2007
DOI: 10.1007/s10571-007-9197-2
|View full text |Cite
|
Sign up to set email alerts
|

Age and Brain Structural Related Effects of Glutaric and 3-Hydroxyglutaric Acids on Glutamate Binding to Plasma Membranes During Rat Brain Development

Abstract: (1) In the present study we determined the effects of glutaric (GA, 0.01-1 mM) and 3-hydroxyglutaric (3-OHGA, 1.0-100 microM) acids, the major metabolites accumulating in glutaric acidemia type I (GA I), on Na(+)-independent and Na(+)-dependent [(3)H]glutamate binding to synaptic plasma membranes from cerebral cortex and striatum of rats aged 7, 15 and 60 days. (2) GA selectively inhibited Na(+)-independent [(3)H]glutamate binding (binding to receptors) in cerebral cortex and striatum of rats aged 7 and 15 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 64 publications
4
7
0
Order By: Relevance
“…Furthermore, excitotoxicity and epilepsy have been related to a diminution of Na + , K + -ATPase activity [54,55]. Our present data, allied to previous works showing that GA and 3HGA inhibit in vitro this enzyme in primary neuronal cultures from chick embryo telencephalon and in rat brain [14,27], as well as alter glutamate uptake and induces glutamate receptor activation [13,15,17,19,20,27,56], reinforce the hypothesis that excitotoxicity may represent an important mechanism of brain damage in GA I.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, excitotoxicity and epilepsy have been related to a diminution of Na + , K + -ATPase activity [54,55]. Our present data, allied to previous works showing that GA and 3HGA inhibit in vitro this enzyme in primary neuronal cultures from chick embryo telencephalon and in rat brain [14,27], as well as alter glutamate uptake and induces glutamate receptor activation [13,15,17,19,20,27,56], reinforce the hypothesis that excitotoxicity may represent an important mechanism of brain damage in GA I.…”
Section: Discussionsupporting
confidence: 90%
“…However, progressive neurological symptoms with mental developmental delay and hypotonia without apparent acute episodes may also occur in a considerable number of patients [5][6][7][8][9]. Neuroradiological imaging shows, besides basal ganglia degeneration, widened Sylvian fissures, cortical atrophy with frontotemporal volume loss, delayed myelination, ventriculomegaly and subdural hemorrhages [1,5,6,8,10,11] Although the pathogenesis of the brain damage in GA I is not fully established, accumulating evidence from in vitro and in vivo experiments performed in brain tissue and cultivated neural cells from rodents and chick suggest that excitotoxicity [6,[12][13][14][15][16][17][18][19][20][21], oxidative stress [22][23][24][25][26][27][28][29][30][31] and cellular bioenergetic dysfunction [2,[32][33][34][35][36][37][38][39] are involved in the brain damage of GA I patients. It is emphasized that these studies were carried out in animal tissues with normal GCDH activity.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] One implication of these findings is that exposure to high levels of KYNA may begin early in life. It is well established that both acetylcholine and glutamate play critical roles in normal brain development [25][26][27] and that NMDA-Rs and a7 nAChRs are involved in synaptic plasticity and neural development. 4,5 Thus, increases in KYNA concentration and the resulting inhibition of NMDA-Rs and/or a7 nAChRs during critical stages of development could have lasting impacts on brain morphology and/or cognitive function in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…A great body of data have suggested that excitotoxicity [8][9][10][11][12][13][14][15][16][17][18], oxidative stress [19][20][21][22][23][24][25][26][27][28] and mitochondrial dysfunction [29][30][31][32][33][34][35][36][37] are involved in the brain injury of GA I. However, the relevance of energy homeostasis disruption in the brain damage in this disease is not yet established.…”
mentioning
confidence: 99%